A concurrent key exchange protocol based on commuting matrices. (28th July 2011) - Almulla, M.; Kanso, A.; Ghebleh, M.; Fouchal, Hacène; Notare, Mirela Sechi Moretti Annoni
SUMMARY In this paper, we suggest a cryptographic protocol for symmetric key exchange based on a set of m commutative square singular matrices of dimension n×n. The suggested scheme provides a concurrent technique for users of symmetric‐key cipher systems to securely exchange their private keys over public channels. This protocol is shown to possess a high level of security based on the algorithm's parameters. We also present a scheme for generating pseudorandom numbers from a single chaotic map for use in various applications, in particular, the suggested key exchange protocol.Copyright © 2011 John Wiley & Sons, Ltd.